Kajian Literatur : Perkembangan Metode Dua Fase dalam Program Linear dan Aplikasinya - Siti Nurmala Sirait; Shilva Syahbina; Widya Putri Mauliza Daulay; Meri Muliani Hasibuan; Siti Salamah Ginting (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Linear programming is one of several methods for finding combinations of numbers to maximize or minimize the objective function in order to produce an optimal solution. However, manual calculations take a long time due to the complexity of the Linear Programming formula. In this paper, the author designs an application to solve web-based Two-Phase Simplex Linear Programming problems using the Angular JavaScript Framework. The application can solve Linear Program problems accurately after the mathematical model is entered. Because the method used is the Simplex Method, the application is also able to solve problems that have more than 3 decision variables. The results obtained are a combination of numbers in the decision variables along with their optimal solutions.